2022
DOI: 10.1007/s10644-022-09457-6
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying causality between oil price and exchange rate in five ASEAN economies

Abstract: The aim of this study is to investigate the effect of oil price changes on the exchange rates of the five ASEAN economies. In the study, a rolling and recursive evolving window algorithm is applied to detect changes in the link between oil price and exchange rate from January 1988 to June 2022 for five ASEAN countries. We extend the existing literature using the Time-varying Granger causality model, which captures sensitivities across various time horizons. The findings revealed heterogeneous effects of oil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 116 publications
1
2
0
Order By: Relevance
“…Our empirical results support the importance of some dates and events in the relationship between exchange and oil markets. This finding is in line with the results of (Kocoglu et al 2023). Moreover, the spillover effect demonstrates diverse illustrations for the oil-exporting countries and oil-importing countries, which confirms the results of (Geng and Guo 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our empirical results support the importance of some dates and events in the relationship between exchange and oil markets. This finding is in line with the results of (Kocoglu et al 2023). Moreover, the spillover effect demonstrates diverse illustrations for the oil-exporting countries and oil-importing countries, which confirms the results of (Geng and Guo 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, they note a negative connection with oil-exporting countries. Kocoglu et al (2023) examine the impact of oil price variations on the exchange rates. They refer to the time-varying Granger causality model.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Running a time-varying analysis, Huang et al (2020) also discover that unexpected oil price shocks have a stronger impact on the main exchange rates compared to general oil price shocks. In the same spirit, Liu et al (2020) indicate that shocks to crude oil prices have immediate and short-term negative impacts on movements of the US exchange rate; Kocoglu et al (2023) revealed heterogeneous effects of oil price on the exchange rate at different time horizons in terms of importance and magnitude over time for Asian countries, and , provide evidence supporting that oil price shocks have a significant time-varying impact on the exchange rate, among which oil demand shock has the most significant effect. Some researchers also rely on the ARDL framework to investigate the intrinsic dynamic between oil prices and exchange rates.…”
Section: Literature Reviewmentioning
confidence: 82%